2014
DOI: 10.1108/ijpdlm-05-2013-0112
|View full text |Cite
|
Sign up to set email alerts
|

“Packaging logistics”: promoting sustainable efficiency in supply chains

Abstract: Purpose – The purpose of this paper is to examine the aspects of internal and external transformation that take place in each company along the supply chain when a “sustainable packaging logistics” approach is implemented. Before this can be achieved, it is necessary to identify and characterise the principal cornerstones and stages associated with this implementation. Design/methodology/approach – In the paper the combination of “case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 34 publications
1
52
0
6
Order By: Relevance
“…Furthermore, the limited shelf life of such kinds of products, the need for a controlled temperature during transportation and storage, the customer demand for high quality and the low profit margins make fresh food distribution a challenging activity that has been studied and analysed in literature from various points of view . Several recent studies have focused particularly on fresh food management and the environmental sustainability of distribution …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the limited shelf life of such kinds of products, the need for a controlled temperature during transportation and storage, the customer demand for high quality and the low profit margins make fresh food distribution a challenging activity that has been studied and analysed in literature from various points of view . Several recent studies have focused particularly on fresh food management and the environmental sustainability of distribution …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, some recent studies promote the development of new sustainable packaging solutions, incorporating an environmental function in addition to the two most traditional functions, marketing and logistics . Moreover, according to some studies, the proposal of such kinds of packaging solutions is one of the most important priorities in designing a new product or its overall supply chain, leading to the introduction of the concept of ‘packaging logistics' …”
Section: Introductionmentioning
confidence: 99%
“…Here, the dependency of logistical and environmental costs is shaped as functions of the 'loss factor,' a parameter adopted to classify means of transport based on loss in transport energy. García-Arca et al (2014) implemented the approach for sustainable packaging logistics to improve the competitiveness of the supply chain. Bing et al (2014) optimized the design of a reverse logistics system, which makes the overall recycling system more efficient and sustainable under the minimization of transportation cost and environmental impact.…”
Section: Sustainable Logisticsmentioning
confidence: 99%
“…According to proposals by García-Arca & Prado-Prado (2008a) and García-Arca et al (2014, four key aspects could be identified in order to promote the development and implementation of 'Packaging Logistics':…”
Section: Developing a "Packaging Logistics" Approachmentioning
confidence: 99%
“…Past research (e.g., Saghir & Jönson, 2001;Klevas, 2005;Hellström & Saghir, 2006;Verghese & Lewis, 2007;García-Arca & Prado-Prado, 2008a;Azzi et al, 2012;García-Arca et al, 2014) consider packaging as one of the key and global elements that support an efficient and sustainable supply chain. These authors show that supply chain companies have different requirements with regard to packaging.…”
Section: Introductionmentioning
confidence: 99%